Social Media Communities as an Example of a New Type of Communication Ecosystem and Society Clustering. - Liu, Zhi-Jiang; Abdullah, Nor'Ain BT; Sokolovskiy, Konstantin; Karabulatova, Irina (Information & Culture, 2025)
The global proliferation of social networks exerts a significant influence on societal development in many countries worldwide. This study aims to conduct a comparative analysis of the key differences in social networks using China as a case study and to explore the global trends in the development of similar networks in other countries around the world. The methodology is based on Spanish sociologist Manuel Castells's theory of network society. Using content analysis of the Sina Weibo social network, data on the hierarchical Dirichlet process were obtained, enabling the assessment of the thematic structure of user information, clustering, and segmentation of popular blogs.